ADHD Treatment with Once-Daily OROS Methylphenidate: Final Results from a Long-term Open-Label Study - Wilens, Timothy; McBurnett, Keith; Stein, Mark; Lerner, Marc; Spencer, Thomas; Wolraich, Mark (Journal of the American Academy of Child and Adolescent Psychiatry, 2005)
Objective: Few studies have assessed effectiveness and tolerability of stimulants when used for prolonged periods in children with attention-deficit/hyperactivity disorder (ADHD). This article presents final results from an open-label, multisite study of a once-daily formulation of methylphenidate (MPH), OROS[R] MPH. Method: Subjects received OROS MPH (18-54 mg initially, with adjustments based on clinical condition) for up to 24 months. Multiple measures of ADHD symptoms, vital signs, weight, height, and laboratory results were assessed throughout the study period. Results: A total of 407 children enrolled in the open-label study and 229 completed the trial. Effectiveness of OROS MPH therapy was maintained throughout the study as indicated by parent and investigator assessments. There was a 26% increase in mean daily dose over the study period, with the majority of the increase occurring during year 1. In general, treatment was well tolerated, with 31 (7.6%) of subjects discontinuing because of adverse events. Minimal effects on growth in height and weight were observed during the study. No clinically significant effects on vital signs or laboratory test parameters were observed. Conclusions: Sustained effectiveness of OROS MPH was maintained for up to 24 months with minimal effects on growth, tics, vital signs, or laboratory test values.